A comparative study of bubble components - Akyüz, Alp Güven Buğra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The co-movement of prices across the world was highlighted during the Credit Crunch of 2008 and the following periods. Since the price drop is attributed to bursting bubbles, it is of interest whether bubbles also follow a diffusion process across countries. This thesis, calculates the bubble percentages using the Kalman Filter approach and runs Granger causality test in order to determine how bubbles spill over across countries. The results suggest that bubbles indeed spill over and the diffusion process is determined by the development level and economic ties of countries rather than geographical proximity. Moreover, bubbles spill over to emerging markets from developed ones and not the other way around. Whereas, the bubbles spill over across developed economies in a bilateral fashion. iv
Keywords: Kalman filtering.